Let x be the number of pounds of the $.20 beans.
The cost of those beans is $.20 * x, or .20x.
Let y be the number of pounds of the $.68 beans. The
cost of those beans is $ .68 * y, or .68y.
We know that 120 pounds of the mix sells for $ 0.54/pound,
for a total of 120 * 0.54 = $ 64.8
x + y = 120
1.35(x) + (1.05)y = 64.8
We can rewrite the first as
x = -y + 120
Now we can substitute (-y + 120) in for (x) in the
second equation, because we just proved they're equal.
.20(x) + .68(y) = 64.8
.20(-y + 120) + .68y = 64.8
-.20y + 24 + .68y = 164.8
-0.3y + 24 = 64.8
-0.38y = -24
y = 63.16